Lansia Rindu Bahagia: Kajian Keluarga Jawa Kelompok Lansia SUCI Banyumanik Semarang - Ayudya Amelia; Afidatul Lathifah; Mudjahirin Thohir (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Happiness is the right of all human beings, children, adults and parents, they have the right to be happy with different sizes of happiness. This difference in the size of happiness is because each individual has different experiences and life patterns so that the assessment of the expected happiness is also different. The research